A comparative analysis on emissions of some next generation long-chain alcohol/diesel blends in a direct-injection diesel engine - Hazrulzurina, Suhaimi; Abdullah, Adam; Mrwan, Anes G.; Zuhaira, Abdullah; Mohd. Fahmi, Othman; Mohd. Kamal, Kamarulzaman; Hagos, F. Y. (AIP Publishing, 2019)
In this experimental study, the effect of alcohols (pentanol and 2-ethyl 1-hexanol) on the emissions were studied and discussed by comparing the results with diesel fuel. 10% pentanol and 10% 2-ethyl 1-hexanol were separately added into 90% diesel fuel which namely as PE10 and HE10, respectively. The tests were performed at full-throttle valve opening and constant engine speed of 1800rpm. The exhaust emissions of diesel engine fuelled with DF, PE10 and HE10 were studied under varies engine loads (0%, 25%, 50%, 75% and 100%). The results show that the use of alcohol fuels affects carbon monoxide (CO) emission to increase as well as hydrocarbon (HC). In addition, decreased nitrogen oxides (NOx) and carbon dioxide (CO2) were observed. Moreover, it is noted that 2-ethyl 1-hexanol was better additives than pentanol due to lower CO, HC and NOx measured in HE10.